Les ateliers d’histoire, issus de l’action citoyenne au coeur des quartiers montréalais - Carbonneau, Réjean (Cap-aux-Diamants, 2022)
Keywords: Atelier d'histoire d'Hochelaga-Maisonneuve; Histoire

La Société des Dix. Explorer la mémoire et l’histoire. - Blais, Christian (Cap-aux-Diamants, 2022)
Keywords: Histoire; Société des Dix

Histoire de la biomédecine au Québec : la physiologie cardio-respiratoire à l'Institut Lavoisier de Montréal (1950-1956) - Ouimet, Benoit (Université du Québec à Montréal, 2022)

It Was a Man's World: Blaine Baker and the Writing of Canadian Legal History, 1981-2018 - Young, Brian (Law, Life, and the Teaching of Legal History. Essays in Honour of G. Blaine Bake, 2022)
Keywords: Ensiegnants; Histoire; Historiens; Université McGill

Une histoire de Montréal. Édition revue et augmentée - Linteau, Paul-André (Boréal compact, 2022)

Histoire et pratique d’érudition au XIXe siècle. Le cas de la Numismatic and Antiquarian Society of Montreal - Vaudry-L., Flavie (Cap-aux-Diamants, 2022)
Keywords: Numismatie

La singularité de l’histoire de la CTCC-CSN (1912-1960) - Rouillard, Jacques (Bulletin d'histoire politique, 2022)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.)

Le pont Royal-Albert, 1875-1876: histoire d'une bérézina sur fond de rivalités ferroviaires - Fougères, Dany (Revue d'histoire de l'Amérique française, 2022)
Keywords: Chemins de fer; Grand Tronc; Ponts

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

Village de Saint-Jean-Baptiste. 160e anniversaire (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Crawford, Alexander

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise; Cecchini, Lisa; Hamilton, Patricia; Knowles, Terry (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Trouve-Toi Une Job ! : Petite Histoire Des Luttes Pour Le Droit À L'assurance-Chômage - Mouvement Action-Chômage Montréal (Écosociété, 2022)
Keywords: Chômage; Groupes populaire

Histoire du Conseil régional FTQ Montréal métropolitain. Les années 1986-2021: Entre persévérance et renouvellement - Bédard, Caroline; Busic, Milan (Service aux collectivités de l'Université du Québec à Montréal, Conseil régional FTQ Montréal, 2022)
Keywords: Fédération des travailleurs et des travailleuses du Québec (FTQ); Grèves; Travail

« Nous ne parlerons pas de la guerre » : la participation oubliée de l’Université de Montréal à la Seconde Guerre mondiale - Walling, Jeremy John (Cahiers d'histoire, 2022)
Keywords: Guerre; Quartier latin (Le); Université de Montréal; Étudiants

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

FAUTEUX, ÆGIDIUS - Lajeunesse, Marcel (Dictionnaire biographique du Canada, 2022)

Le Deuxième front de la CSN. Des gains importants. Un échec - Rioux, Michel (Bulletin d'histoire politique, 2022)
Keywords: Confédération des syndicats nationaux

La contribution de la CSN à la défense et la promotion du droit à la santé et la sécurité dans le monde du travail au Québec - Rioux, Claude (Bulletin d'histoire politique, 2022)
Keywords: Confédération des syndicats nationaux; Travail

Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan M. (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Astronomie; Géologie; Notman, William; Photographie

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

Éclairer et perfectionner l’esprit : l’éducation libérale et le délicat compromis entre raison et foi dans les écoles classiques de langue anglaise au Bas-Canada (1800-1840) - McCutcheon, Shawn (Études d'histoire religieuse, 2022)
Keywords: Langue; Libéralisme

La question de la confessionnalité scolaire dans la revue catholique Maintenant (1965-1975) - Lafontaine, Anthony M. (Études d'histoire religieuse, 2022)
Maintenant est une revue catholique québécoise fondée par les Dominicains et publiée de 1962 à 1975 en collaboration avec des laïcs. Ses animateurs et animatrices, qui adhèrent à la philosophie du personnalisme de même qu’à la théologie de la sécularisation, appartiennent au milieu intellectuel catholique critique de la présence institutionnelle de l’Église au Québec. Cet article vise à présenter l’évolution de leur lutte contre cette « chrétienté » et du raisonnement qui la sous-tend durant les années 1960 ainsi que la conclusion à laquelle les auteurs et autrices en arrivent dans la seconde moitié de cette décennie, soit un appui clair à la sécularisation des institutions publiques. Cette dernière est présentée dans les pages de la revue comme étant la seule voie d’avenir pour le catholicisme en cette période de modernisation rapide, c’est-à-dire qu’elle représente la solution au phénomène du décrochage religieux qui les inquiète. , Maintenant is a French Canadian Catholic paper created by the Dominican Order and published from 1962 to 1975 in collaboration with laypeople. Its authors belong to the circle of Catholic intellectuals critical of the Church’s institutional presence in Quebec in the 1950s and 1960s. The present article seeks to present their analysis of Quebec’s religious decline and highlights how their theological ideas influence their stance in favour of the secularization of the province’s public institutions. Through this, it will become evident that secularization is Maintenant ’s answer to the religious crisis of the 1960s and 1970s; its authors see it as the only way forward for Catholicism in the modern age.
Keywords: Maintenant (revue)

La CSN et la condition des femmes : d’une approche de protection à un engagement actif et militant envers l’égalité - Carbonneau, Claudette (Bulletin d'histoire politique, 2022)
Keywords: Confédération des syndicats nationaux; Femmes

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Logement

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d'histoire de l'Amérique française, 2022)
Keywords: Femmes; Montreal Light, Heat and Power; Travail; École ménagère; Électricité

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Quand les éléphants s'amenaient dans Rosemont - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Cirque; Photographie; Poirier, Conrad

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Artisans; Carrière; Charretiers; Travail

Les premières institutions bancaires de la rue Masson - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Banque Canadienne nationale; Banque d'Hochelaga; Banque de Montréal; Banques

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

Aux origines du village de Saint-Jean-Baptiste, 1850-1861 - Robert, Jean-Claude (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

Fletcher's Field flanc est du Mont Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Funiculaire; Mont Royal; Mont-Royal (parc); Parcs; Rues; Variole; Épidémies

La carrière Rhéaume 1909-1937 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Rosemont

En 1909 découverte d'une voûte mystérieuse dans le quartier Rosemont - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Rosemont

Un arrondissement parsemé d'anciennes carrières - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Parcs; Rosemont

La Côte-de-Saraguay - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Côtes; Saraguay; Villages

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

Les débuts de la poste à Ahunstic-Cartierville - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Bordeaux; Cartierville; Poste; Sault-au-Récollet

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

Back River Memorial Gardens - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Cimetières; Juifs

Saint-André-Apôtre. La vie communautaire s’organise - Ménard, Céline (Au fil d’ABC / SHAC, Société d’histoire d’Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Caisses populaires; Groupes populaires

Les élections au temps des patriotes : conflits, violence et politisation en contexte électoral (1820-1834) - Théberge, Samuel (Université du Québec à Montréal, 2022)
Keywords: Minerve (La); Montreal Gazette; Montreal Herald; Élections

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

Les témoins et la justice militaire pendant les Rébellions au Bas-Canada, 1837-1839 - Lafond, François (Université Laval, 2022)
Keywords: Rébellions

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

La pathologisation des accouchements de jumeaux au Québec, 1930-1980 - Forget, Karine (Université du Québec à Trois-Rivières, 2022)
Keywords: Enfants; Hôpitaux

'' Une lamentable tragédie '' : la représentation des homicides québécois dans la presse francophone et anglophone au Québec entre 1885 et 1915 - Pilote, Gina (Université Laval, 2022)
Keywords: Criminalité; Montreal Gazette; Presse (La)

Former et être formée au travail domestique : l'enseignement ménager et la couture à l'école publique québécoise (1937-1969) - Brisebois, Marilyne (Université Laval, 2022)
Keywords: Commission des écoles catholiques de Montréal; Femmes; Étudiants

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

Femmes, réseaux et subversion : l'organisation féministe de l'avortement illégal au Québec (1969-1988) - Raby, Marie-Laurence (2022)
Keywords: Avortement; Femmes; Féminisme

Remembering the Duvalier era: Resistance, Exile, and Solidarity in the Life Stories of Haitian-Montrealers - Riou, Geneviève (Université Concordia, 2022)
Keywords: Haïtiens

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

''L’autisme, cet inconnu'' : représentations expertes et populaires du trouble du spectre de l’autisme dans les quotidiens montréalais de 1970 à 1998 - El-Sabbagh, Marianne (Université de Montréal, 2022)
Keywords: Devoir (Le); Presse (La)

« Il y a plus de crime à détruire un enfant, qu'à le faire » : traitement communautaire et judiciaire de l'infanticide en Nouvelle-France (1671-1747) - Chasle, Ariane (Université de Montréal, 2022)
Keywords: Criminalité; Enfants; Tribunaux

Construire une citoyenneté urbaine par le droit de vote au municipal: lois électorales et contestations militantes à Montréal de 1965 à 1974 - Robert, Vincent (Université de Montréal, 2022)
Keywords: Femmes; Libéralisme; Montreal Local Council of Women; Rassemblement des citoyens et citoyennes de Montréal; Élections

Les sports d'hiver (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2022)
Keywords: Carnaval; Hockey; Parcs; Patin; Plateau Mont-Royal (arrondissement)

Prohibition-Brasserie Chapman-Microbrasseries - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2022)
Keywords: Alcool; Brasserie; Prohibition

Cent ans de théâtre sur le Plateau (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2022)
Keywords: Plateau Mont-Royal (arrondissement); Radio; Théâtre; Théâtre du Rideau vert; Tremblay, Michel

A very Partisan Press - Bérubé, Harold (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Avenir (L'); La Fontaine, Louis-Hippolyte; Minerve (La); Montreal Gazette; Montreal Herald; Papineau, Louis-Joseph; Partis politiques

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Sainte-Anne (marché)

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Hôtellerie; Marchés

A Building Transformed. From Market to Parliament - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

Moving the Seat of Parliament. From Kingston to Montréal - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Kingston to Montréal. Inside the Parliamentary Libraries - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Discovering Parliament in Montréal - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

In Response to the Unrest, Petitions in Support of the Queen Poured in. Denouncing the Tories to Save the Empire - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Mouvement annexionniste; Parlement; Réformistes; Torys; Émeutes

After the Fire Comes the Investigation. Citizens Give Testimony - Roy, Alain; Horner, Dan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

Rebellion Losses Bill: Mere Pretext or the Real Cause of the Burning of Parliament - Leblanc, Jean-François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Rébellions; Réformistes; Torys; Émeutes

1849. To the Parliament House! - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail